Divergência genética de genótipos de feijoeiro a infestação de Zabrotes subfasciatus (Bohemann) (Coleoptera: Bruchidae) - Costa, Eduardo Neves [UNESP]; Sardinha de Souza, Bruno Henrique [UNESP]; Bottega, Daline Benites [UNESP]; Oliveira, Flavia Queiroz de [UNESP]; Ribeiro, Zulene Antonio [UNESP]; Boica Junior, Arlindo Leal [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The aim of this work was to evaluate the genetics divergence of bean genotypes in relation to the oviposition, feeding and development of Zabrotes subfasciatus, determining the degrees of resistance to the weevil. The genotypes used were: IAC Carioca-Tybata, IAC Fortaleza, IAPAR 81, IAC Carioca-Ete, IAC Galante, IAC Harmonia, IAC Una, IAC Diplomata, BRS Supremo and RAZ 49. Tests were performed in laboratory under controlled humidity, temperature and photophase conditions. In free choice test, 10 g of bean genotypes seeds were distributed in circular openings placed equidistant from each other in aluminum trays, where 70 couples were released. The attractiveness was evaluated 24 hours and seven days after the experiment started, and then the number of eggs was evaluated. In non choice test, 10 g of seeds were used where seven couples of Z. subfasciatus, 24 hours-old, were released, remaining seven days, and after the adults retreat, the total number of eggs, viable and unviable eggs, the number and percentage of emerged adults, weight, longevity and period from egg to adult of males and females, sex ratio, dry mass and dry mass consumed by insect were evaluated. In the genotype IAC Harmonia was observed the lower oviposition; RAZ 49 was the most non preference-type resistant for feeding and/or antibiosis-type resistant; BRS Supremo, IAC Carioca-Ete and IAPAR 81 are no preference for feeding and/or antibiosis-type moderate resistant; IAC Galante is susceptible and the other genotypes are highly susceptible to Z. subfasciatus.
Genetic divergence of bean genotypes to infestation of Zabrotes subfasciatus (Bohemann) (Coleoptera: Bruchidae)
Keywords: Antibiosis; weevil; stored grains; Phaseolus vulgaris; Plant resistance to insects